The use of pulmonary function test to predict occupational lung disease among workers in steel industry - Ibrahim, Wisam Nabeel; Ibrahim, Nabeel; Issa, Layla (2013)
Occupational lung diseases are a group of illnesses that are caused by repeated and continuous long term exposure to dusts, gases, vapors and fumes at work that can lead to respiratory system injuries.[1] Substances which are known to cause occupational lung diseases include asbestos, polycyclic hydrocarbons and radon in mines sulphur dioxide, chlorine, ammonia, oxides of nitrogen, mineral dust, [1]. Exposure to these irritant particles can cause several different types of lung diseases ranging from mild asymptomatic bronchial inflammation to advance stage of pulmonary fibrosis and bronchial carcinoma [2]. The range of injuries depend on size of the particles, large particles are deposited in the nose and upper air way, while small particles roughly between one and seven microns have a good chance of reaching and depositing in the alveoli [3].